Second Chance My Life in Things - Rosengarten, Ruth (Open Book Publishers, 2022)
In this intimate memoir, Ruth Rosengarten explores the subject of evocative objects through a series of interconnected essays. Evocative objects reflect our attitudes to our own lives and how we seek to display ourselves to ourselves. They are therefore, closely linked to our memories, and how we filter, process and reconstruct them. Rosengarten explores the themes and associations invoked by her own evocative objects, which are frequently shabby things of no material value. They are, importantly, often objects that, in their materiality, bear traces of actions, of something-having-been. Through the associative pathways that these objects have paved, she discusses her experiences with the losses she has undergone, her family's migrations, and what it means to be a childless woman. This leads her to address the question of what will become of her storied objects and the memories attached to them when she is no longer in existence. This memoir offers an interdisciplinary approach to collecting and compiling fragments of one's life, paying close attention to the evocative objects that embody us. In doing so, these essays explore loss, memory, childlessness, longing, family history, literature and art theory through material entities which reveal the immaterial 'things' at the heart of this study. This book is sure to be of interest to anyone stimulated by memory work and the relationship between humans and their possessions.